1999
DOI: 10.1074/jbc.274.22.15473
|View full text |Cite
|
Sign up to set email alerts
|

The Compact Conformation of Fibronectin Is Determined by Intramolecular Ionic Interactions

Abstract: Fibronectin exists in a compact or extended conformation, depending upon environmental pH and salt concentration. Using recombinant fragments expressed in bacteria and baculovirus, we determined the domains responsible for producing fibronectin's compact conformation. Our velocity and equilibrium sedimentation data show that FN2-14 (a protein containing FN-III domains 2 through 14) forms dimers in low salt. Experiments with smaller fragments indicates that the compact conformation is produced by binding of FN1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
217
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(223 citation statements)
references
References 34 publications
6
217
0
Order By: Relevance
“…Additional decreases in FRET at Ͼ2 M Gdn⅐HCl indicated further Fn unfolding. In these stronger denaturing conditions, it has been shown that Fn modules progressively unfold (17). Thus, decreases in FRET at Ͼ2 M Gdn⅐HCl were likely the result of donor-acceptor separation caused by module unfolding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional decreases in FRET at Ͼ2 M Gdn⅐HCl indicated further Fn unfolding. In these stronger denaturing conditions, it has been shown that Fn modules progressively unfold (17). Thus, decreases in FRET at Ͼ2 M Gdn⅐HCl were likely the result of donor-acceptor separation caused by module unfolding.…”
Section: Resultsmentioning
confidence: 99%
“…The first model proposes that Fn dimers within fibrils are structured such that their N-terminal regions are aligned with the fibril axis, and C-terminal regions fold on themselves normal to the fibril axis. Mechanical tension pulls the molecule into alignment with the fibril axis, causing the fibril to stretch (14,17). According to this model, the level of FRET in fibrillar Fn-D͞A under tension should be larger or equal to that of Fn-D͞A extended with its FnIII modules intact-the level of FRET in 0.5 M to 2 M Gdn⅐HCl, 60% to 75% (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The compact conformation of FN dimers is maintained by intramolecular interactions involving the type III 12-14 repeats of FN. 53,54 The type III [12][13][14] repeats, also known as heparin II binding domain, interact with the HS chains from various members of the Sdc family. 55 Binding of Sdc1 with heparin II may facilitate unfolding of dimeric FNs and expose FN self-assembly (FN-binding) sites, thus promoting FN deposition and fibrillogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Under physiological conditions, FN adheres more strongly in its compact conformation on hydrophobic surfaces 39 , which may also cause subsequent denaturation of the FN secondary structure to increase substrate binding affinity 40 . The compact conformation of FN is stabilized by intermolecular bonds 41 but can be disrupted by interacting surface groups, particularly hydrophilic and negatively charged surfaces, causing the protein to adopt a more unfolded conformation 25,42 . In this conformation, the protein can interact via different domain regions that are specific to various ECM proteins (e.g.…”
Section: Resultsmentioning
confidence: 99%